Boosting energy storage performance of BiFeO3-based multilayer capacitors via enhancing ionic bonding and relaxor behavior. Issue 13 (4th March 2022) - Zhu, Li-Feng; Song, Aizhen; Zhang, Bo-Ping; Gao, Xiao-Qi; Shan, Zhi-Hang; Zhao, Gao-Lei; Yuan, Junqi; Deng, Deng; Shu, Hailong; Li, Jing-Feng
Abstract : F-BT- x NT MLCCs were designed and expected to achieve high energy-storage density because of ultrahigh P s value of BiFeO3 system. With enhancement of ionic bonding and dielectric relaxation, excellen U rec = 9.1 J cm −3 and η > 80% were achieved at x = 0.12. Abstract : Environmentally friendly BiFeO3 capacitors have great potential for applications in pulsed-discharge and power conditioning electronic systems because of their excellent intensity of spontaneous polarization ( P s ). Herein, (0.7− x )BiFeO3 -0.3BaTiO3 - x NaTaO3 + 0.3 wt% MnO2 (abbreviated as BF-BT- x NT) multilayer ceramic capacitors (MLCCs) were designed and prepared to improve the energy storage performance via enhancing ion bonding and dielectric relaxation. The BDS of BF-BT- x NT MLCCs from 500 kV cm −1 at x = 0.05 increases greatly to 800 kV cm −1 at x = 0.15 due to the increase of the band gap and resistance, and the decrease of dielectric permittivity. An excellent energy storage density U rec = 9.1 J cm −3 and efficiency η > 80% were obtained since ultrahigh BDS (780 kV cm −1 ) and low P r value (2.1 μC cm −2 at measured electric field 780 kV cm −1 ) were achieved simultaneously in BF-BT- x NT multilayer capacitors at x = 0.12. This work provides a strategy for improving energy storage properties of BiFeO3, which is via enhancing ionic bonding and relaxor behavior to achieve high BDS, low P r and large P max, simultaneously.